Emergency satellite solutions - Bjorgo, Einar; Pisano, Francesco (Technical Centre for Agricultural and Rural Cooperation, 2008)
Getting precise information during a conflct or emergency means relief organizations can take quick and effective decisions. UNOSAT analyses satellite data to give disaster managers the details they need.